Notes from a Cuban Diary: Forty Women Speak on Forty Years - Joanne Elvy (Adult Education Research Conference, 2004)
Many consider the 1961 Literacy Campaign—Campaña de Alfabetización—to be the backdrop for social, economic, cultural and ethical transformations that occurred in Cuba following 1959. The Campaña marked a definitive moment of liberation for Cuban women, as more than half of the volunteers were those who left their family homes to live and work with the illiterate in the countryside. This research features photographic portraits of women who participated as literacy teachers, together with a series of reflective testimonies as textural components.